Is there a link between air pollution and mental disorders? - Buoli, Massimiliano; Grassi, Silvia; Caldiroli, Alice; Carnevali, Greta Silvia; Mucci, Francesco; Iodice, Simona; Cantone, Laura; Pergoli, Laura; Bollati, Valentina (Environment international, 2018)
Several studies have demonstrated the association between air pollution and different medical conditions including respiratory and cardiovascular diseases. Air pollutants might have a role also in the etiology of mental disorders in the light of their toxicity on central nervous system. Purpose of the present manuscript was to review and summarize available data about an association between psychiatric disorders and air pollution. A research in the main database sources has been conducted to identify relevant papers about the topic. Different air pollutants and in particular PM and nitric oxides have been associated with poor mental health; long exposition to PM2.5 has been associated with an increased risk of new onset of depressive symptoms (Cohen's effect size d: 0.05–0.81), while increased concentration of nitric dioxide in summer with worsening of existing depressive conditions (Cohen's effect size d: 0.05–1.77). However, the interpretation of these finding should take into account the retrospective design of most of studies, different periods of observations, confounding factors such as advanced age or medical comorbidity. Further studies with rigorous methodology are needed to confirm the results of available literature about this topic. •Air pollution contributes to the etiology of different medical conditions.•Air pollutants may have a potential role in the onset or worsening of mental conditions.•More consistent data regard the association of depression with air pollutants.•High quality studies are needed to confirm poor mental health due to air pollution.